Instagram and TikTok: The role of women in social media - Gil Ibáñez, Marta; Ruiz Viñals, Carmen; del Olmo Arriaga, Jose Luis (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The purpose of this study is to analyze policies related to women promoted by the social media platforms TikTok and Instagram. A qualitative research has been conducted using documentary analysis complemented with a focus group study to female university students in order to incorporate their point of view on the regulation and accountability in the contents published on these platforms. One of the aims is to see how it affects the sexist attitudes they contain. The results highlight important shortcomings of the social network platforms analyzed in relation to the role that women play on these platforms.